2015
DOI: 10.1111/dote.12349
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and reproductive factors and risk of esophageal cancer in women: a meta-analysis

Abstract: Currently published studies on the relationship between hormonal and reproductive factors and esophageal cancer (EC) risk in women have yielded contradictory findings. For a better understanding of this relationship, we first performed this meta-analysis by pooling all available publications. Sixteen independent studies were retrieved after a comprehensive search in PubMed and Embase databases. The pooled relative risks (RRs) with 95% confidence intervals (95% CIs) were calculated. The pooled RRs implicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 30 publications
0
29
3
Order By: Relevance
“…Although some studies failed to show a significant impact of estrogen on pancreatic 20 or bladder cancers, 21 the preventive effect of estrogen against liver cancer in the current study and in others studies was observed for gastric 22 distal large bowel cancer 23 , and esophageal cancers 24 , with an average risk reduction of 28%, and the estimated ORs (95% CI) were .77 (.64–.92) and .68 (.48–.97), respectively. In contrast, estrogen use was significantly associated with increased risk of breast cancer.…”
Section: Discussioncontrasting
confidence: 57%
“…Although some studies failed to show a significant impact of estrogen on pancreatic 20 or bladder cancers, 21 the preventive effect of estrogen against liver cancer in the current study and in others studies was observed for gastric 22 distal large bowel cancer 23 , and esophageal cancers 24 , with an average risk reduction of 28%, and the estimated ORs (95% CI) were .77 (.64–.92) and .68 (.48–.97), respectively. In contrast, estrogen use was significantly associated with increased risk of breast cancer.…”
Section: Discussioncontrasting
confidence: 57%
“…However, an inverse association was observed between parity and EA. A meta‐analysis by Wang et al . reported no association for EA with reproductive factors; however, this analysis did show an inverse association between breastfeeding and EA .…”
Section: Discussioncontrasting
confidence: 55%
“…A meta‐analysis by Wang et al . reported no association for EA with reproductive factors; however, this analysis did show an inverse association between breastfeeding and EA . A recent meta‐analysis reported an inverse association between breastfeeding, parity and esophageal cancer…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The systematic epidemiological studies suggest that BRCA1 and BRCA2 are important susceptibility genes of familial breast cancer [26]; however, population and hospital-based studies indicate that mutations in these two genes account for only 4–6% of total breast cancer cases [7, 8]. Other susceptibility factors that contribute to breast cancer have been identified as being related to exposure to environmental carcinogens (including certain chemicals and ionizing radiation), as well as increasing age, family and reproductive history, obesity, heavy alcohol intake and hormonal replacement therapy [919]. There is considerable inter-individual variation in their susceptibility to environmental carcinogens.…”
Section: Introductionmentioning
confidence: 99%